The imilla of Paucartambo (Cusco) and the milieu incarnation: a case about transvestism and androgyny in the Andes - Levin, Yiftah (2021)
The present article proposes that the imilla of Paucartambo, Cusco, is a transvestite and transgender character that constitute an interpretation of the theme of gender in the Andes. The question is: who is the imillla, and why is it traditionally embodied by a man?  It is argued that the participation of the imilla in the performance of ritual and play and its symbolism, is essential in the Qhapaq Qolla and the fiesta of the Virgen del Carmen of Paucartambo, as representative of its cultural environment. As a liminal character, the imilla is unique in the fiesta; and it constitute a unique case in the transvestite and transgender representationes of the Andes, as far as we know. Finally, it is argued that as a transgender character, the imilla embodies the entire concept of Paucartambo as a nucleus, as it is narrated in the myths and performed during the guerrilla.